Development of Guided Inquiry-Based Digestive System Teaching Materials to Improve Critical Thinking and Scientific Attitudes - Afridah, Ayu; Iswari, Retno Sri; Lisdiana, Lisdiana (Universitas Negeri Semarang, 2022)
Difficulty in understanding the material and the decline in student learning outcomes can be managed by developing teaching materials tailored to the needs of students. This study aims to develop guided inquiry-based digestive system teaching materials as a source of student learning to improve student's critical thinking and scientific attitude. The method used in this research is the Research and Development (R&D) with the steps used are: 1) Identify potential and problems; 2) collecting data; 3) product design; 4) design validation; 5) main product revision design; 6) small-scale trial; 7) second product revision; 8) wide-scale test; 9) product revision; 10) final product. Class Students research subjects XI MIPA 4 and XI MIPA 5 SMAN 5 Cirebon with 60 students as subject. The results showed: (1) guided inquiry-based teaching material products developed based on the guided inquiry syntax; (2) the validity of teaching materials based on the validation scores of material and media experts, respectively 95% and 96.25% with very valid criteria; (3) guided inquiry-based teaching materials based on results of the analysis of the description test and the analysis of the scientific attitude assessment question, it shows that teaching material effectively improve the learning outcomes of student’s critical thinking and scientific attitude. Based on the results of the study, it can be concluded that the digestive system teaching materials developed have characteristics based on the guided inquiry syntax, including: formulate the problem, make a hypothesis, planning an experiment, collecting data and conclusion, very valid and effective teaching materials improve critical thinking and scientific attitude of students.